2014
DOI: 10.1530/joe-13-0311
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolic effects of 3-iodothyronamine in hepatocytes

Abstract: 3-Iodothyronamine (T 1 AM) is an endogenous relative of thyroid hormone with profound metabolic effects. In different experimental models, T 1 AM increased blood glucose, and it is not clear whether this effect is entirely accounted by changes in insulin and/or glucagone secretion. Thus, in the present work, we investigated the uptake of T 1 AM by hepatocytes, which was compared with the uptake of thyroid hormones, and the effects of T 1 AM on hepatic glucose and ketone body production. Two different experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…Recent LC-MS/MS investigations of TH or TAM were based on direct injection of diluted cell lysates and/or cell culture media (w/o FCS) without analyte extraction [25,26,27]. Sample preparation (solid-phase extraction, SPE, liquid-liquid extraction or online SPE) prior to LC-MS/MS analysis can improve solid and high RE with a minor ME, while preventing accelerated deterioration of analytical columns and contamination of the LC-MS/MS system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent LC-MS/MS investigations of TH or TAM were based on direct injection of diluted cell lysates and/or cell culture media (w/o FCS) without analyte extraction [25,26,27]. Sample preparation (solid-phase extraction, SPE, liquid-liquid extraction or online SPE) prior to LC-MS/MS analysis can improve solid and high RE with a minor ME, while preventing accelerated deterioration of analytical columns and contamination of the LC-MS/MS system.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate IS can compensate for the alteration of analytes in complex matrices during sample preparation, adhesion effects or ion suppression during electrospray ionization during the MS measurement by coelution from the LC [12] . Recent LC-MS/MS investigations of TH or TAM were based on direct injection of diluted cell lysates and/or cell culture media (w/o FCS) without analyte extraction [25][26][27] . Sample preparation (solid-phase extraction, SPE, liquid-liquid extraction or online SPE) prior to LC-MS/MS analysis can improve solid and high RE with a minor ME, while preventing accelerated deterioration of analytical columns and contamination of the LC-MS/MS system.…”
Section: Discussionmentioning
confidence: 99%
“…Among these new compounds, analogue 2 was synthesized to evaluate the effects induced by the recovery of the phenolic function as in T1AM. Additionally, to gain further insights on how the pattern of substitutions modulate the SG-analogues potency as mTAAR1 agonists, we investigated the following structure modifications: (a) the introduction of small alkyl substituents (Me, i-Pr) on both outer and inner rings (4, 6−10), (b) the removal of the methylene bridge, producing the diaryl analogues 5 and 6, (c) the introduction of a biguanide moiety at the oxy-alkyl side chain (15,16), and finally (d) mono-and bis-N-acetylation (3, 9−15). This last chemical modification has been suggested by a recent study conducted by Hoefig et al, 6 showing that O-acetyl and N-acetyl derivatives of T1AM may be found in white adipose tissue and liver endogenous cells.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 4a, treatment of HepG2 cells with T1AM (0.1, 1, and 10 μM) confirmed the bell-shaped dose−response curve observed in our previous study. 16 To better define the dose dependence of 1 and 2 effects on glucose production, additional experiments were carried out using a wider range of doses for both compounds. As shown in Figure 4b, the EC 50 calculated for the effect on gluconeogenesis was in the submicromolar range for 2, and in the supramicromolar range for 1.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation